FROZEN STORAGE STUDIES OF COMPOSITE FISH MINCE FROM DHOMA (SCIAENID SP. ) AND LACTARIUS (LACTARIUS LACTARIUS) - AGARWAL, ANIL; RAGHUNATH, M R; SOLANKI, K K (Fishery Technology, 2017)
Fish minces fromDhoma and Lactarius were mixed in the ratio of 40:60 respectively, and quick frozen along with individual minces at -40Â°C and stored at -20Â°C. Shclf-lif e was evaluated by following biochemical, physical and organoleptic changes -0ccured during storage upto 44 weeks. Rapid decreases were noted in water soluble nitrogen and salt soluble nitrogen fractions during the initial period of 16 weeks. A good correlation was observed between changes :i.n salt-soluble nitrogen and organoleptic evaluation. The mincef, were in good and acceptable condition up to 32 weeks of storage.